Analisis Analisis Manajemen Pembelajaran Seni Tari Berbasis Seni Pertunjukan dalam Upaya Kreativitas dan Inovasi Siswa SMK - Retno Setyomurti (Universitas Sarjanawiyata Tamansiswa, 2022)
This research aims to obtain management of dance art learning, obtaining analysis of students' creativity and innovation in performing arts-based dance art learning, acquire analysis of supporting factors, inhibitors and solutions in the management of dance art-based dance learning in an effort to creativity and innovation of students. The method used with qualitative desceptive methods. The data sources is the head teachers and students. The data collection techniques are using observation, interview and documentation techniques. The validity of the data is triangulation of sources, techniques and time. Data analysis use data collection, data reduction, data presentation, and conclusion drawing. The results is the analysis of dance art learning management there is planning, organizing, implementation, evaluation and implementation is good. Creativity and innovation analysis shows that SMK 1 Kasihan students have creativity skills is good in learning by being matched with creativity indicators and students have innovations that are relative, compatible, not complexity, triability and observability. Supporting factors in the management of dance art learning based on performing arts are facilities and infrastructure and relationships. The inhibitory factors that exist in the form of time owned both by teachers in school and in determining the dress rehearsal / dirty in the staging. The solution in dealing with obstacles is that teachers and students work together in maximizing their time.